Deciphering Molecular Mechanisms Involved in Salinity Tolerance in Guar (Cyamopsis tetragonoloba (L.) Taub.) Using Transcriptome Analyses - Biswa R. Acharya; Devinder Sandhu; Christian Dueñas; Jorge F. S. Ferreira; Kulbhushan K. Grover (Plants, 2022)
Guar is a commercially important legume crop known for guar gum. Guar is tolerant to various abiotic stresses, but the mechanisms involved in its salinity tolerance are not well established. This study aimed to understand molecular mechanisms of salinity tolerance in guar. RNA sequencing (RNA-Seq) was employed to study the leaf and root transcriptomes of salt-tolerant (Matador) and salt-sensitive (PI 340261) guar genotypes under control and salinity. Our analyses identified a total of 296,114 unigenes assembled from 527 million clean reads. Transcriptome analysis revealed that the gene expression differences were more pronounced between salinity treatments than between genotypes. Differentially expressed genes associated with stress-signaling pathways, transporters, chromatin remodeling, microRNA biogenesis, and translational machinery play critical roles in guar salinity tolerance. Genes associated with several transporter families that were differentially expressed during salinity included ABC, MFS, GPH, and P-ATPase. Furthermore, genes encoding transcription factors/regulators belonging to several families, including SNF2, C2H2, bHLH, C3H, and MYB were differentially expressed in response to salinity. This study revealed the importance of various biological pathways during salinity stress and identified several candidate genes that may be used to develop salt-tolerant guar genotypes that might be suitable for cultivation in marginal soils with moderate to high salinity or using degraded water.